Feminist Activism, Travel and Translation Around 1900 Transnational Practices of Mediation and the Case of Käthe Schirmacher - Gehmacher, Johanna (Translation History, 2024)
"How did feminist ideas travel in an age of growing nationalism, imperial powerplay and entrenched inequalities? Feminist Activism, Travel and Translation brilliantly foregrounds the work done by translation, focusing on the first generation of university-educated women. Käthe Schirmacher's life illustrates the promise and the painful fragility of early feminism. Gehmacher shows the active role translation played in liberal, revolutionary and ultranationalist movements, shaping the new public spheres of this historical moment." -Lucy Delap, Professor of Modern British and Gender History, University of Cambridge, UK "This groundbreaking study examines the transfer of ideas, mediation, and translation as transnational practices of the international women's movement around 1900. The differing expectations of translations and translators as well as Western dominance in transnational communication are convincingly brought out. Gehmacher, the best connoisseur of Käthe Schirmacher's estate, introduces with this book a fresh perspective on the history of the international women's movement." -Angelika Schaser, Professor of Modern History, Universität Hamburg, Germany This open access book takes the biographical case of German feminist Käthe Schirmacher (1865-1930), a multilingual translator, widely travelled writer of fiction and non-fiction, and a disputatious activist to examine the travel and translation of ideas between the women's movements that emerged in many countries in the late 19th and early 20th century. It discusses practices such as translating, interpreting, and excerpting from journals and books that spawned and supported transnational civic spaces and develops a theoretical framework to analyse these practices. It examines translations of literary, scholarly and political texts and their contexts. The book will be of interest to academics as well as undergraduate and postgraduate students in thefields of modern history, women's and gender history, cultural studies, transnational and transfer history, translation studies, history and theory of biography. Johanna Gehmacher is Professor of Modern and Gender History at the University of Vienna, Austria.